Nguyễn Thi, viết ở chiến trường - Lưu, Khánh Thơ.; Phong Lê. (Nhà xuất bản Trẻ : Hội nghiên cứu & giảng dạy văn học TP. HCM, 2005)
Literary criticism on Nguyen Thi's works.
Includes bibliographical references (page 164).
Literary criticism on Nguyen Thi's works.
Keywords: Criticism, interpretation, etc. / fast / (OCoLC)fst01411635